2020
DOI: 10.3758/s13414-020-02018-x
|View full text |Cite
|
Sign up to set email alerts
|

Priors and payoffs in confidence judgments

Abstract: Priors and payo↵s are known to a↵ect perceptual decision-making, but little is understood about how they influence confidence judgments. For optimal perceptual decision-making, both priors and payo↵s should be considered when selecting a response. However, for confidence to reflect the probability of being correct in a perceptual decision, priors should a↵ect confidence but payo↵s should not. To experimentally test whether human observers follow this normative behavior for natural confidence judgments, we cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
4
14
0
Order By: Relevance
“…Other studies have suggested that perceptual and postperceptual biases can be distinguished by their different effects on confidence ratings: While perceptual biases typically induce shifts in confidence, response biases (induced for instance by changing the payoff structure of the task) do not necessarily do so (Gallagher et al, 2018(Gallagher et al, , 2019; see also Locke et al, 2020).…”
Section: Empirical Cases Of Perceptual Criterion Shiftsmentioning
confidence: 99%
“…Other studies have suggested that perceptual and postperceptual biases can be distinguished by their different effects on confidence ratings: While perceptual biases typically induce shifts in confidence, response biases (induced for instance by changing the payoff structure of the task) do not necessarily do so (Gallagher et al, 2018(Gallagher et al, , 2019; see also Locke et al, 2020).…”
Section: Empirical Cases Of Perceptual Criterion Shiftsmentioning
confidence: 99%
“…Namely, the need for our sense of confidence to best reflect the true probability of being correct, as sacrificing some gains for better accuracy may foster more accurate judgements of perceptual confidence (Locke, Gaffin-Cahn, Hosseinizaveh, Mamassian, & Landy, 2020). The payoffs of a task can influence confidence ratings (Lebreton et al, 2018;Locke et al, 2020) despite not changing that probability that the decision was correct. For example, this can be an overconfidence when reporting the highly-rewarded stimulus and underconfidence when reporting the low-reward option.…”
Section: Need For Accuracymentioning
confidence: 99%
“…Additionally, confidence judgements, on the correctness of their decision, could be included after every trial. Standard extensions of the SDT framework for confidence would then reveal if that observer let the rewards influence their confidence (Locke et al, 2020). If affective bias is driven by a need for high accuracy, we would see the anxiety/mood disorder individuals giving greater preference for being correct over earning more reward and being more susceptible to letting reward influence their sense of confidence.…”
Section: Proposed Need-for-accuracy Testmentioning
confidence: 99%
“…In the case of categorical confidence judgements (e.g., binary report, scale, etc. ), additional confidence criteria delineate the mapping between distance and confidence [ 6 , 7 , 21 ]. Most DFC-metric models also allow this sensory measurement to differ from that used for the perceptual decision [ 22 ], either by additional confidence noise corrupting the measurement [ 23 25 ] and/or from altering the measurement with parallel decision processes [ 7 , 26 ].…”
Section: Introductionmentioning
confidence: 99%